2000
DOI: 10.1016/s0926-860x(00)00416-6
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation of Ni–Mo/Al2O3 catalysts aged in a commercial reactor during the hydrotreating of deasphalted vacuum residuum

Abstract: A series of Ni-Mo/Al 2 O 3 catalysts for the hydrotreating of deasphalted vacuum bottoms has been investigated as fresh catalysts and after aging in an industrial reactor during a typical commercial run. Several structural parameters have been varied in the catalyst series. In particular, pore size, surface area, active metal loading and pellet size were changed to investigate the role of kinetic and diffusional phenomena present in this process. The samples were placed in different locations along the industr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 13 publications
3
8
0
Order By: Relevance
“…Metal and coke deposition show contrary trends; while the former is high at the beginning and then it decays, the latter starts low and then it rises, consistently with profiles previously reported [1,2,29,31,32,34]. Both hard and soft coke amounts also increase toward the bed outlet, although the soft/hard ratio seems constant through the entire bed.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Metal and coke deposition show contrary trends; while the former is high at the beginning and then it decays, the latter starts low and then it rises, consistently with profiles previously reported [1,2,29,31,32,34]. Both hard and soft coke amounts also increase toward the bed outlet, although the soft/hard ratio seems constant through the entire bed.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies on deactivation by metals and coke in hydroprocessing catalysts have been reported [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Nonetheless, only few studies on deactivation pattern along residue hydrotreating bench-scale reactor have been published [29][30][31][32]. In this paper, the catalyst deactivation of the first stage of a hydrotreating bench-scale reactor is analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Pore volume loss data in Table 3 indicate that the volume of pore in <10 nm size and pores in 10-20 nm size are easily affected while the macro pore volume changes little [37][38][39], resulting in a larger average pore diameter of spent catalysts compared to the fresh ones [23,40]. Isaza et al reported that small pores were blocked and some of large pores were partially blocked under the reaction conditions [15]. The PSD of regenerated catalyst A0 and A7 in Fig.…”
Section: Characterization Of Fresh Spent and Regenerated Catalystsmentioning
confidence: 94%
“…Referring to the parameters that impact on the HDM activity, many factors may be considered such as the chemical characteristics of the feed, the pore structure, active metal loading, surface area and pellet size of the catalyst, as well as the position along the packed-bed reactor [15]. In our study, we use the same feedstock, the same active metal loading on different catalysts and the same pellet size of catalysts.…”
Section: The Optimum Psd For the Metal Removalmentioning
confidence: 99%
See 1 more Smart Citation